2020
DOI: 10.18632/aging.103645
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the clinical value and potential mechanisms of AHNAK2 in papillary thyroid carcinoma

Abstract: Background: AHNAK2 has been recently reported as a biomarker in many cancers. However, a systematic investigation of AHNAK2 in papillary thyroid carcinoma (PTC) has not been conducted. Results: AHNAK2 is overexpressed in PTC tissues and could be an independent prognostic factor. AHNAK2 expression was significantly high in patients with advanced stage, advanced T classification, lymph node metastasis, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…As a diagnostic marker, AHNAK2 could immunohistochemically differentiate between inflammatory changes and carcinoma in situ (CIS) [ 18 ]. In terms of the prognostic value, only a few studies have been performed and reported that a higher expression of AHNAK2 was associated with shorter overall survival in BCa [ 13 , 19 ]. However, these previous studies were based on gene enrichment analyses and focused on an association between gene types and survival duration without adjusting clinical information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a diagnostic marker, AHNAK2 could immunohistochemically differentiate between inflammatory changes and carcinoma in situ (CIS) [ 18 ]. In terms of the prognostic value, only a few studies have been performed and reported that a higher expression of AHNAK2 was associated with shorter overall survival in BCa [ 13 , 19 ]. However, these previous studies were based on gene enrichment analyses and focused on an association between gene types and survival duration without adjusting clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…Pan-cancer analyses revealed the functional roles of AHNAK2 in the epithelial-mesenchymal transition (EMT), which plays a key role as a tumor promoter by allowing epithelial cells to gain a range of mesenchymal characteristics [ 13 , 14 ]. Analyses based on clinical specimens showed that AHNAK2 regulated the EMT via a TGF-β/Smad3 pathway in lung adenocarcinoma and a hypoxia inducible factor-1α/zinc finger E-box-binding homeobox 1 (HIF-1/ZEB1) pathway in clear cell renal cell carcinoma [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bioinformatics reports have identified the important roles of immune-related biomarkers in PTC pathogenesis, such as AHNAK nucleoprotein 2 (AHNAK2), angiotensin II receptor type 1 (AGTR1), etc. ( Li et al, 2021 ; Lin et al, 2019 ; Xie et al, 2020b ; Xue, Li & Lu, 2020 ). In patients with PTC, M2 macrophages, Tregs, monocytes, neutrophils, DCs, MCs, and M0 macrophages appeared to play a tumor-promoting role, while M1 macrophages, CD8 + T cells, B cells, NK cells, and T follicular helper (TFH) cells might play an anti-tumor part ( Xie et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Two members comprise the AHNAK protein family, which are AHNAK and AHNAK2: 5 AHNAK plays a protective role in vascular healing after wire injury and contributes to muscular dystrophies when it is abnormally located in muscle connective tissues, 6,7 whereas AHNAK2, originally found in mouse heart tissue extract and gradually reported in recent years, 5 is involved in cell migration, repair and other processes. [8][9][10][11] AHNAK2 is regarded as an oncogenic protein and plays a role in the metastases of cancers, including pancreatic ductal adenocarcinoma, clear cell renal cell carcinoma, uveal melanoma, and papillary thyroid carcinoma, [12][13][14][15] and some studies have revealed its possible mechanism in tumors. Kirov et al have indicated that AHNAK2 is an important element of the fibroblast growth factor1 nonclassical export pathway, which regulates carcinogenesis, angiogenesis, and inflammation, 16 Li et al reported that it promotes uveal melanoma progression by regulating the PI3K signaling pathway, 14 and Wang et al revealed that AHNAK2 mediates hypoxia pathway-driven epithelial-mesenchymal transition (EMT) and induction of stem cell properties by targeting hypoxia-inducible factor 1 (HIF1)-α in clear cell renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%